MazeMaster - Mohammad Salman; Mohammad Najjar (My University, 2024)
This project aims to design a maze solving robot that operates with left wallfollowing algorithm . The robot is built with a combination of hardware components, including DC motors, ultrasonic sensors, a microcontroller, and some other sensors and electrical components to navigate and solve mazes . The left wall-following algorithm ensure that the robot is continuously follows the left wall of the maze until it reaches the goal . This method is efficient for structured maze environments where the goal is to find the black carpet at the end of maze. A significant feature of the robot is the integration of the web interface that allows the user to control the robot remotely . The web interface enables the user to start , stop the robot with simple commands , providing flexibility in operation. the interface displays the temperature around the robot . This temperature monitoring capability can be useful for some applications , such as informing the user of the situation inside the maze (for rescue applications) , detecting heat sources or ensuring that the robot is operating within safe temperature limits. The robot is equipped with an ultrasonic sensor array to detect walls and obstacles, ensuring to navigation through the maze without hitting the walls . The left wall-following algorithm is implemented in the robot's microcontroller , allowing it to make decisions on turns and movements based on the distance to the walls . The web interface is designed for ease of use , with responsive controls and ambient temperature display.